Strengthening Pokdarwis Institutions as a Strategy for Developing Mangrove Ecoedutourism in Tluwuk Village, Pati Regency - Saputro, Danang Dwi; Gustaman, Fulia Aji; Indardi, Nanang (Jurnal Abdimas, 2025)
This community service program aimed to strengthen the institutional capacity of the Tourism Awareness Group (Pokdarwis) “Karya Pamuji Agung” in managing the mangrove-based tourism potential in Tluwuk Village, Pati Regency, through organizational development and the formulation of Standard Operating Procedures (SOP) based on the ecoedutourism concept. The main issues identified included weak organizational management, the absence of tourism management SOPs, and limited promotional and visitor service skills. The implementation was carried out through stages of socialization, training, mentoring, and evaluation using the Participatory Rural Appraisal (PRA) approach to ensure active community involvement. The results indicated improved competence among Pokdarwis members in planning programs, understanding the principles of the tourism sapta pesona, and applying four SOPs covering general tourism services, mangrove edutourism, birdwatching, and salt production tourism. This program has enhanced the group’s organizational structure and management capabilities, enabling Pokdarwis Karya Pamuji Agung to act as a community-based driving force for sustainable mangrove ecoedutourism development in Tluwuk Village.